Foreign-owned plants and job sevurity - Bellmann, Lutz; Andrews, Martyn; Schank, Thorsten; Upward, Richard (Review of World Economics, 2012)
We investigate the hypothesis that workers in foreign-owned establishments face greater job insecurity. Using linked employer employee data from Germany, we examine whether foreign-owned establishments are more likely to exit production, and whether workers in foreign-owned establishments face higher separation rates, net of establishment exit. We find that, after controlling for the different characteristics of foreign and domestic establishments, foreign establishments have higher exit rates and higher separation rates, but the effect is quantitatively small. In contrast, foreign-owned establishments which do not export appear to have considerably higher exit rates and separation rate
WiSo-Import:2015-03-26:3631